2021
DOI: 10.1108/jfc-09-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Fraudulent financial reporting motivations in emerging markets

Abstract: Purpose The purpose of this paper is to study comparatively motivations for committing fraud in financial statements in two emerging markets including Iran and Iraq. Design/methodology/approach The research is a descriptive survey and statistical population consists of independent auditors. The field survey and questionnaire were used for data collection. Findings Findings can raise auditors’ awareness of management fraud motivations. It can help regulators and authorities in both countries as well as othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
2
0
2
Order By: Relevance
“…Laporan keuangan pada perusahaan dijadikan sebagai alat ukur oleh pemegang saham, investor ataupun kreditur bank untuk mengambil keputusan (Eryigit, 2019;Mattei, 2023;Ngah, 2021;Sun, 2019;Svabova, 2020;Zhang, 2022;Zin, 2020). Faktor yang dapat mempengaruhi kecurangan pelaporan keuangan adalah salah satunya adanya tekanan (Demetriades, 2022;Rostami, 2022;Sallal, 2021;Shakouri, 2021;Tarjo, 2022). Tekanan merupakan situasi dimana manajemen atau pegawai lainnya merasakan insentif atau tekanan untuk melakukan kecurangan.…”
Section: Pendahuluanunclassified
“…Laporan keuangan pada perusahaan dijadikan sebagai alat ukur oleh pemegang saham, investor ataupun kreditur bank untuk mengambil keputusan (Eryigit, 2019;Mattei, 2023;Ngah, 2021;Sun, 2019;Svabova, 2020;Zhang, 2022;Zin, 2020). Faktor yang dapat mempengaruhi kecurangan pelaporan keuangan adalah salah satunya adanya tekanan (Demetriades, 2022;Rostami, 2022;Sallal, 2021;Shakouri, 2021;Tarjo, 2022). Tekanan merupakan situasi dimana manajemen atau pegawai lainnya merasakan insentif atau tekanan untuk melakukan kecurangan.…”
Section: Pendahuluanunclassified
“…Berdasarkan kasus-kasus yang terjadi perilaku hedonism memiliki kecenderungan mengarahkan ke sikap hedonisme yang akan memicu terjadinya kecurangan. Shonhadji & Maulidi (2021); Smaili et al, (2021); Sallal et al, (2021); Dempere (2021); Prastika (2018) menemukan bahwa gaya hidup hedonisme berpengaruh positif terhadap kecurangan akademik. Penelitian serupa juga dilakukan oleh Sartika & Hudainah (2018) yang menemukan bahwa gaya hidup hedonis berpengaruh positif terhadap intensi korupsi.…”
Section: Pendahuluanunclassified
“…audit process. Studies have identified the factors influencing fraudulent reporting incentives as management structure and organizational culture (Badawi, 2008), analyzed the relationship between earnings management incentives and weak corporate governance (Hasnan et al, 2013), the failure of analysts' forecasts in Iraq's economic environment, taking revenge in Iran's economic environment (Sallal et al, 2021), and reward and tax avoidance (Widuri et al, 2019). Also, some other studies have been conducted that focus on the factors affecting audit quality.…”
Section: Introductionmentioning
confidence: 99%